Memories of an Expatriate in Malaysia يوميات من وجع الغربة بماليزيا - Chtaibi, Khalid (Foundation Zahmah Kuttab for Culture and Publication- Egypt, 2018)
Memories of an Expatriate in Malaysia A new literary book of satirical fiction, printed and published by Foundation Zahmah Kuttab for Culture and Publication The book's anecdotes and oddities in an interesting and enjoyable comedic style qualify it to be transformed into a scenario for a distinguished creative work of art. The events of the book present Malaysia in a different way, covering the issues of the Arabic community in Malaysia, with all its negatives and positives, in a strikingly creative and exciting way. The book consists of 3 parts: 1- Hamouda daily adventures 2- Arabic Ambassador stories 3- Arab Cultural Salon Nights in Kuala Lumpur